2017
DOI: 10.3748/wjg.v23.i23.4285
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging may predict deep remission in patients with perianal fistulizing Crohn's disease

Abstract: AIMTo evaluate the imaging course of Crohn’s disease (CD) patients with perianal fistulas on long-term maintenance anti-tumor necrosis factor (TNF)-α therapy and identify predictors of deep remission.METHODSAll patients with perianal CD treated with anti-TNF-α therapy at our tertiary care center were evaluated by magnetic resonance imaging (MRI) and clinical assessment. Two MR examinations were performed: at initiation of anti-TNF-α treatment and then at least 2 years after. Clinical assessment (remission, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 47 publications
1
26
1
Order By: Relevance
“…A fistula was defined as “closed” in the absence of drainage, with gentle finger compression on examination. Nine papers defined “remission” as closure of all baseline fistulas; six studies required this over two consecutive evaluations and three at a single time point . Eight studies assessed for clinical “response.” This was defined as closure of ≥50% of baseline fistulas at a single time point in three papers, and across two consecutive visits in three papers .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A fistula was defined as “closed” in the absence of drainage, with gentle finger compression on examination. Nine papers defined “remission” as closure of all baseline fistulas; six studies required this over two consecutive evaluations and three at a single time point . Eight studies assessed for clinical “response.” This was defined as closure of ≥50% of baseline fistulas at a single time point in three papers, and across two consecutive visits in three papers .…”
Section: Resultsmentioning
confidence: 99%
“…Nine papers defined “remission” as closure of all baseline fistulas; six studies required this over two consecutive evaluations and three at a single time point . Eight studies assessed for clinical “response.” This was defined as closure of ≥50% of baseline fistulas at a single time point in three papers, and across two consecutive visits in three papers . In two papers, it was defined as either closure of ≥50% baseline draining fistulas or marked reduction in drainage of all fistulas with less pain and induration, as reported by the patient, across two consecutive visits …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T2-weighted magnetic resonance imaging (MRI) with fat-suppression is considered the gold-standard for fistula imaging and an MRI-based score is currently available for defining disease activity, although it is still not widely used in clinical practice[ 1 ]. Thomassin et al[ 11 ] have recently showed that deep remission, defined as a composite clinical (absence of any draining fistulas and self-reported drainage episodes by the patient at two successive evaluations), endoscopic (absence of ulcers in the anal canal) and radiological (absence of T2 hyperintensity and contrast enhancement on MRI) remission, was achieved in approximately one-third of patients with perianal fistulizing CD[ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although several variables have been associated with improved outcomes (Table 2 ), prediction of deep remission remains a challenge. Thomassin et al[ 11 ] have recently identified absence of rectal involvement on MRI (OR = 4.6; 95%CI: 1.03-20.5) as the only variable associated with deep remission in patients with perianal fistulizing CD[ 11 ]. Similar to ulcerative colitis and luminal CD[ 19 - 25 ], recent data demonstrate that higher infliximab concentrations are associated with better clinical outcomes in patients with perianal fistulising CD[ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%